Innovations in competitive manufacturing - Swamidass, Paul M. (New York : AMACOM, 2002)
This title is an examination of manufacturing innovations - both technical and knowledge-based. It examines the elements that make today's manuacturers successful. Many examples from industry throughout the book should enable the reader to appreciate and comprehend the concepts presented.
Includes bibliographical references and index.
oif 11/11/14
Loan
Keywords: Production management; Manufactures -- Technological innovations -- Management; Industrial management; Competition